DISADVANTAGES OF THE PROCEDURAL REGULATION OF THE SEARCH IN LIGHT OF PROTECTING HUMAN RIGHTS AND FREEDOMS - Zhirova, M.I; Kondratiuk, S.V (LLC (EOOD) "SCIENTIFIC CHRONOGRAPH", 2019)
A search is a complex investigative action in both the procedural and psychological aspects of its production. This is due to both a large number of procedural requirements for its implementation, and a lot of moral issues related to the forced seizure of objects and documents, restrictions of human rights and freedoms. The article is devoted to a number of questions of the search, which require more precise regulation in the Russian Federation Code of Criminal Procedure in the light of the protection of human rights and freedoms. Based on the provisions of international acts and the Constitution of the Russian Federation it is shown that the improvement of the procedural order of the search is today an urgent need so as to law enforcement practice should fully meet the high standards of protection of human rights and freedoms. In particular, it is proposed to specify in the law the definition of the purposes and grounds for the search. Legislative fuzzy definition of these categories entails the adoption of arbitrary, unreasonable decisions about the search. The authors believe that the actual basis for the search can only be information obtained by procedural means. In order to preserve information that is a secret to the privacy of the participants of the search it is necessary to introduce a restriction on the circle of persons who may be involved as witnesses and also determine the limits of fixing the circumstances of the private life of citizens in respect of whom a search is being conducted in the search report or other materials of the criminal case. The article also proposes an author's solution to the question of the possibility of a search of a house in the absence of persons living in it.